2022
DOI: 10.1158/1541-7786.mcr-21-0672
|View full text |Cite
|
Sign up to set email alerts
|

MUC1-C Dictates JUN and BAF-Mediated Chromatin Remodeling at Enhancer Signatures in Cancer Stem Cells

Abstract: The oncogenic MUC1-C protein promotes dedifferentiation of castrate-resistant prostate cancer (CRPC) and triple-negative breast cancer (TNBC) cells. Chromatin remodeling is critical for the cancer stem cell (CSC) state; however, there is no definitive evidence that MUC1-C regulates chromatin accessibility and thereby expression of stemness-associated genes. We demonstrate that MUC1-C drives global changes in chromatin architecture in the dedifferentiation of CRPC and TNBC cells. Our results show that MUC1-C in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 46 publications
1
58
0
Order By: Relevance
“… 66 MUC1-C forms complexes with JUN and ARID1A in promoting chromatin accessibility of NOTCH1 and other stemness-associated genes in CRPC cells. 23 In the present work, we found that MUC1-C, JUN and ARID1A form a complex on the IFNGR1 dELS region that induces chromatin accessibility, H3K4 trimethylation and IFNGR1 expression. These findings provided direct evidence for a MUC1-C-induced pathway that integrates induction of ARID1A/BAF with intrinsic activation of the CSC state 23 and IFN-γ pathway in CRPC progression ( Figure 9 ).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“… 66 MUC1-C forms complexes with JUN and ARID1A in promoting chromatin accessibility of NOTCH1 and other stemness-associated genes in CRPC cells. 23 In the present work, we found that MUC1-C, JUN and ARID1A form a complex on the IFNGR1 dELS region that induces chromatin accessibility, H3K4 trimethylation and IFNGR1 expression. These findings provided direct evidence for a MUC1-C-induced pathway that integrates induction of ARID1A/BAF with intrinsic activation of the CSC state 23 and IFN-γ pathway in CRPC progression ( Figure 9 ).…”
Section: Discussionsupporting
confidence: 54%
“…Along these lines, nuclear MUC1-C forms complexes with JUN/AP-1 (Supplemental Fig. S1e) 23 and we detected occupancy of MUC1-C and JUN on the IFNGR1 dELS region ( Figure 2d ). Consistent with JUN-mediated recruitment of the BAF chromatin remodeling complex, 44 we also detected occupancy of ARID1A ( Figure 2d ).…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The COMPASS family replaces PcG-driven repressive marks by inducing H3K4 methylation and transcriptional activation [ 53 ] . Emerging evidence indicates that MUC1-C plays a role in driving H3K4 trimethylation of enhancer-like signatures of stemness-associated genes [ 57 ] . Additional studies will therefore be needed to determine whether MUC1-C activates COMPASS and thereby the H3K4me3 mark on these target genes.…”
Section: Muc1-c Drives Lineage Plasticity and Epigenetic Remodeling I...mentioning
confidence: 99%